2017
DOI: 10.1002/oby.21783
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index trajectories of Indigenous Australian children and relation to screen time, diet, and demographic factors

Abstract: ObjectiveLimited cross‐sectional data indicate elevated overweight/obesity prevalence among Indigenous versus non‐Indigenous Australian children. This study aims to quantify body mass index (BMI) trajectories among Indigenous Australian children aged 3‐6 and 6‐9 years and to identify factors associated with the development of overweight/obesity.MethodsThree‐year BMI change was examined in up to 1,157 children in the national Longitudinal Study of Indigenous Children. BMI trajectories among children with normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…The finding that early socio‐economic disadvantage is associated with lower BMI is consistent with previous reports of lower BMI among younger Aboriginal and Torres Strait Islander children in more disadvantaged regions . This contrasts with the inverse relationship between socio‐economic advantage and BMI in children and young people in the broader Australian population, but is consistent with the socio‐economic patterning of BMI among children in low and middle income countries .…”
supporting
confidence: 89%
“…The finding that early socio‐economic disadvantage is associated with lower BMI is consistent with previous reports of lower BMI among younger Aboriginal and Torres Strait Islander children in more disadvantaged regions . This contrasts with the inverse relationship between socio‐economic advantage and BMI in children and young people in the broader Australian population, but is consistent with the socio‐economic patterning of BMI among children in low and middle income countries .…”
supporting
confidence: 89%
“…Thirteen cross-sectional and five longitudinal were included. Thirteen [ 14 , 15 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] examined children and adolescent populations aged between 4–18 years and five studies [ 13 , 39 , 40 , 41 , 42 ] examined adult populations. One [ 26 ] examined older adolescents and adults aged 16–65 years.…”
Section: Resultsmentioning
confidence: 99%
“…obesity, smoking and diabetes during pregnancy) are common in the Indigenous Australian population; [47][48][49][50][51][52][53] these factors are therefore likely to contribute to the high prevalence of overweight and obesity observed among Aboriginal and Torres Strait Islander children. 53 Longitudinal analysis of LSIC data by Thurber et al 54 has also identified a high prevalence of obesity among Aboriginal and Torres Strait Islander children in the first years of life, and a rapid onset of overweight and obesity from age 3 to 9 years. In addition, this research identified the potential role of sugar-sweetened beverage consumption in contributing to the rapid development of obesity among Aboriginal and Torres Strait Islander children.…”
Section: Obesitymentioning
confidence: 99%
“…In addition, this research identified the potential role of sugar-sweetened beverage consumption in contributing to the rapid development of obesity among Aboriginal and Torres Strait Islander children. 54 Thurber et al have also explored the social, cultural and environmental context of dietary behaviours, with analysis showing that sugarsweetened beverage consumption is shaped by social and environmental factors such as housing and parental education, 55 and that many social, cultural and environmental barriers prevent optimal intake of fruits and vegetables. 56 Major life events and mothers' mental health SEWB for Aboriginal and Torres Strait Islander children and families encompasses mental health as well as broader components such as spiritual, cultural and social well-being, and overall community well-being.…”
Section: Obesitymentioning
confidence: 99%